Pengaruh Citra Merek, Harga, dan Kelengkapan Produk terhadap Keputusan Pembelian di Ramayana Tanjungpinang - Miranda Miranda; Iranita Iranita; Roni Kurniawan (Indo Publishing, 2026)
This study aims to determine the influence of brand image, price, and product completeness on purchasing decisions at Ramayana Tanjungpinang. The background of this study is based on the phenomenon that a high number of consumer visits is not always followed by optimal purchasing decisions. This research employed a quantitative method with an explanatory approach. Data were collected through questionnaires distributed to 96 respondents who had made purchases at Ramayana Tanjungpinang. The data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, partial testing (t-test), simultaneous testing (F-test), and coefficient of determination (R²). The results showed that brand image did not have a significant effect on purchasing decisions. Meanwhile, price and product completeness had a positive and significant effect on purchasing decisions. Simultaneously, brand image, price, and product completeness had a positive and significant effect on purchasing decisions at Ramayana Tanjungpinang. The Adjusted R Square value of 0.722 indicates that 72.2% of the variation in purchasing decisions can be explained by brand image, price, and product completeness, while the remaining 27.8% is influenced by other factors outside this study. The findings indicate that price and product completeness are the most influential factors in improving consumer purchasing decisions at Ramayana Tanjungpinang.